Uncertainties and validation of alien species catalogues: The Mediterranean as an example. (15th May 2017) - Zenetos, Argyro; Çinar, Melih Ertan; Crocetta, Fabio; Golani, Dani; Rosso, Antonietta; Servello, Gianna; Shenkar, Noa; Turon, Xavier; Verlaque, Marc
Abstract: The meticulous revision by taxonomic experts of established alien species in the Mediterranean resulted in a major revision of the list proposed by Galil et al. (2016), with 73 species to be excluded (35 species categorised as non-established and 37 as not true aliens), and 72 species added to the list. Consequently, by year 2016 the total number of established alien species in the Mediterranean reached 613, which is a 28% increase over the preceding four years. If we also consider casual species (208 species), the total number of alien species in the Mediterranean is 821. This is attributed to: new findings, change in establishment status of species previously known on the basis of few and scattered records, and results of phylogenetic studies in some cosmopolitan species. However, the true number of alien species reported here is considered to be an underestimation, as it does not include phytoplanktonic organisms, Foraminifera, cryptogenic and species known on the basis of questionable records that might turn out to be true aliens. EASIN and INVASIVESNET can play a major role in the future revision/update of the present list, which currently serves for assessing indicators that are necessary for policy, and for management of alien species in the Mediterranean Sea. An increasing trend in new arrivals since 1950, which culminated in the 2001–2010 period, appeared to decline after 2010. Whether this negative trend is an indication of improvement, or is an artefact, remains to be seen. The current list provides a reliable updated database from which to continue monitoring the arrival and spread of invasive species in the Mediterranean, as well as to provide counsel to governmental agencies with respect to management and control. Current geographical, taxonomical and impact data gaps can be reduced only by instituting harmonised standards and methodologies for monitoring alien populations in all countries bordering the Mediterranean Sea.